Speleoclimate Monitoring to Assess Cave Tourism Capacity in Gelatik Cave, Gunungsewu Geopark, Indonesia - Eko Bayu Dharma Putra; Danardono Danardono; Eko Haryono; Emilya Nurjani; Muhammad Iqbal Taufiqurahman Sunariya (Forum Geografi, 2018)
Increased of the number of visitor at Gelatik Cave is a challenge in terms of cave management. In natural conditions, Caves are vulnerable with environmental changes especially microclimates condition. The change of microclimate inside the cave can destruct cave ornaments.Therefore, it is necessary to calculate the cave carrying capacity with microclimates as the main parameter. This research aims to (1) explore the daily variation of speleoclimate in Gelatik Cave Tourism and (2) analyze the cave tourism capacity in Gelatik Cave. Microclimate parameter that was measured in this research was temperature, relative humidity, and carbon dioxide inside the cave. Measurement of microlimate parameter was carried out automatically for 24 hours during peak season in December 2017 and low season in May 2018. Cave tourism capacity was measured using Lobo method (Lobo, 2015). The results showed that temperature, relative humidity, and carbon dioxide in the Gelatik Cave varry due to tourism activities. The most sensitive parameter is the carbon dioxide concentration inside the cave. The maximum of tourists allowed to visit Gelatik Cave is 76 visitors/ day during holidays and working days. Meanwhile, the maximum time of stay accepted for a particular area inside Gelatik Cave is 17 minutes 10 seconds during weekdays and 12 minutes 53 seconds during the holiday season.